2010
DOI: 10.1111/j.1750-8606.2010.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Eat in an Obesogenic Environment: A Developmental Systems Perspective on Childhood Obesity

Abstract: Abstract— Currently, children are developing in an obesity‐promoting, or obesogenic, environment, which has emerged within the past 3 decades. This rapid change provides a rare opportunity to investigate the phenotypic outcomes that result from the expression of human genetic predispositions in a new environment. Unfortunately, the environmental changes that have occurred are associated with epidemic obesity rates in all age groups. Using a developmental perspective, this article argues that this probabilistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
105
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(111 citation statements)
references
References 61 publications
(69 reference statements)
3
105
1
2
Order By: Relevance
“…These statistics are of particular concern because obese preschool-age children are 5 times more likely to be overweight during adolescence (Birch & Anzman, 2010) and more than 4 times as likely to be obese adults when compared to their normal weight counterparts (Gluckman, Hanson, Cooper, & Thornburg, 2008). These results show that, contrary to popular belief, children do not "grow out of" their "baby fat."…”
contrasting
confidence: 58%
“…These statistics are of particular concern because obese preschool-age children are 5 times more likely to be overweight during adolescence (Birch & Anzman, 2010) and more than 4 times as likely to be obese adults when compared to their normal weight counterparts (Gluckman, Hanson, Cooper, & Thornburg, 2008). These results show that, contrary to popular belief, children do not "grow out of" their "baby fat."…”
contrasting
confidence: 58%
“…12 The current Western diet is obesogenic because foods and beverages high in sugar, and foods with added salt are readily available. 15 There are some evidence that dietary fatty acid composition can influence plasma 16,17 and adipose tissue fatty acid composition, 17 which, in turn, can modify inflammation 14,18 and inflammationmediated disease. 14 Specifically, it has been suggested that high dietary intake of specific fatty acids may stimulate IL-6 secretion, and, in contrast, high intakes of n-3 PUFAs may inhibit low-grade inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many of the children are school age or adolescents, beyond the age when food preferences and eating behaviors are being formed. 18 Thus, the aims of this study are to determine whether an association exists between fathers' and children's body mass index (BMI), diet quality, and physical activity duration and intensity level. It was hypothesized that fathers' BMI, diet quality, and physical activity amount by intensity level would be significantly, positively related to children's BMI z score, diet quality, and physical activity amount by intensity level, respectively.…”
mentioning
confidence: 99%